Peculiarities of the Partisan Movement on the Karelian Front During the Great Patriotic War - Verigin Sergey Gennadyevich (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2015)
Based on the analysis of the archival sources and scientific literature, the peculiarities of the partisan movement on the Karelian Front during the Great Patriotic War are described in the article. The partisan units of the Karelian Front were based not on the territory occupied by the enemy (as in the other regions of the USSR), they were located across the Karelian Front line and raided on the territory occupied by the enemy and then after accomplishment of the military mission they returned to the rear area of the Soviet troops. Much attention is given to the raids of the partisan units into the border territory of Finland and their effectiveness in the framework of the whole fight against the enemy on the Karelian Front. A point of view of the Finnish researchers on that issue is under consideration, as it focuses attention only on one aspect of the problem – the consequences of the partisan raids for the Finnish civilians. The inquiry of the partisan movement on the Karelian Front during the Great Patriotic War is summarized; the prospects of the further research connected with formation of the joint Russian-Finnish projects and using new archival sources from the Russian and Finnish funds are planned.